Efficacy and safety of pharmacological and non-pharmacological therapies in Lennox-Gastaut syndrome: a systematic review and network meta-analysis - Zhu, Zhengyan; Zhang, Zhenpan; Xiao, Wei; Wang, Chunhua; Liang, Risheng (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to evaluate the efficacy and safety of antiepileptic drugs and non-pharmacological treatments in patients with Lennox-Gastaut syndrome (LGS).MethodsWe conducted a systematic search of the PubMed, Embase, Cochrane, and Web of Science databases for randomized controlled trials (RCTs) evaluating both pharmacological and non-pharmacological interventions for LGS. The treatments assessed included cannabidiol, fenfluramine, clobazam, rufinamide, felbamate, lamotrigine, topiramate, deep brain stimulation, and anterior corpus callosotomy. The primary efficacy outcome was defined as a reduction of at least 50% in the frequency of drop seizures during treatment compared to baseline levels. The secondary efficacy outcome was measured as the median percentage reduction in monthly drop seizure frequency throughout the treatment period. Safety assessments were based on the incidence of adverse events and serious adverse events. All outcomes were ranked according to their surface under the cumulative ranking curve (SUCRA).ResultThis network meta-analysis encompassed 12 RCTs involving a total of 1,445 patients. The SUCRA indicated that clobazam 1 mg/kg/day, anterior corpus callosotomy, and rufinamide were the three most effective interventions for achieving a reduction of at least 50% in drop seizures. In terms of median percentage reduction in drop seizure frequency, clobazam 1 mg/kg/day ranked highest, followed by clobazam 0.5 mg/kg/day and rufinamide. Regarding safety profiles, SUCRA analysis revealed that cannabidiol 20 mg/kg/day had the highest likelihood of inducing adverse events, followed closely by fenfluramine 0.7 mg/kg/day. Lamotrigine was found to be most likely to cause serious adverse reactions, with cannabidiol 10 mg/kg/day following closely behind.ConclusionClobazam 1 mg/kg/day, anterior corpus callosotomy, and rufinamide manifested the most optimal efficacy in seizure control among LGS patients. Caution should be exercised when administering cannabidiol, lamotrigine, and fenfluramine 0.7 mg/kg/day in clinical practice to mitigate safety concerns associated with drug-related side effects.